Cardiovascular adverse events in chronic myeloid leukemia patients treated with nilotinib or imatinib: A systematic review, meta-analysis and integrative bioinformatics analysis - Li, Sicong; He, Jinshan; Zhang, Xinyi; Cai, Yuchun; Liu, Jian; Nie, Xiaoyan; Shi, Luwen (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of this article is to assess the risk and potential mechanisms of cardiovascular adverse events in patients treated with nilotinib or imatinib by conducting a systematic review, meta-analysis and integrative bioinformatics analysis. Materials and methods Three databases were systematically searched for studies published from inception to May 29, 2022. Differential expression analysis and weighted gene coexpression network analysis (WGCNA) were performed to search for modules of genes most associated with cardiotoxicity. Protein-protein interaction (PPI) network analysis was then performed to identify hub genes for the cardiotoxicity of nilotinib. Molecular docking was used to analyze the effects of rosuvastatin and aspirin on these targets. Results Patients treated with nilotinib as first-line treatment were associated with a higher risk of CAE (OR = 3.43 [95% CI 2.77–4.25]), CAD (OR = 5.30 [95% CI 3.85–7.29]), ACS (OR 2.7 [95% CI 1.60–4.54]), CVA (OR 5.76 [95% CI 2.84–11.28]), PAOD (OR 5.57 [95% CI 3.26–9.50]) and arrhythmia (OR 2.34 [1.17,4.67]) than those treated with imatinib, while no significant difference was found in the risk of HF (OR 1.40 [95% CI 0.42–4.69]) between the two groups. Patients who were treated with more than 600 mg daily dosage of nilotinib or followed up for more than 5 years had a higher risk of ACS and CVA. IL6, CXCL8, CCL2, SOD2, NFKBIA, and BIRC3 were identified as the top 6 hub genes in the magenta module (human cardiomyocyte samples) and were mainly enriched in the NOD-like receptor signaling pathway, IL-17 signaling pathway, TNF signaling pathway, lipid and atherosclerosis signaling pathway. TYROBP and CSF1R were identified as hub genes in the turquoise module (liver samples from Mus musculus). GSEA results showed that type II diabetes mellitus, B-cell receptor, apoptosis, insulin, natural killer cell mediated cytotoxicity, mTOR, chemokine, and T-cell receptor signaling pathways were related to the higher risk of atherosclerosis caused by nilotinib. Rosuvastatin can effectively bind to most of the hub targets and proteins enriched in the inflammatory pathways above. Conclusion CML patients who start with nilotinib have a higher risk of CAE than those with imatinib. Atherosclerosis caused by the inflammatory response and glycolipid metabolism disorder is the key mechanism of nilotinib cardiotoxicity. Rosuvastatin may be an effective treatment for the cardiotoxicity of nilotinib.